2023
DOI: 10.32859/era.26.15.1-24
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plant use and integration of traditional healers into health care system: A case study at Ankasa Forest Reserve and catchment communities in Ghana

Abstract: Background:The study documented the medicinal plants used to treat diseases and assessed the level of integration of traditional medicine practice (TMP) into the health care delivery system in the study area.Methods: A structured questionnaire was purposively used to select informants from Ghana Federation of Traditional Medicine Practitioners Association. The ethnographic method using a semi-structured questionnaire, interviews and group discussions was employed to collect data for assessing level of integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Species were conserved to sustain the long-term use of plant species due to the existing harvesting practices (Kunwar et al, 2016). However, the frequent collection and use of plant roots and stems for ethnomedicine in traditional practices (e.g., P. mira and P. utilis) may pose sustainability concerns (Essandoh et al, 2023).…”
Section: Medicinal Use Of Eoppsmentioning
confidence: 99%
“…Species were conserved to sustain the long-term use of plant species due to the existing harvesting practices (Kunwar et al, 2016). However, the frequent collection and use of plant roots and stems for ethnomedicine in traditional practices (e.g., P. mira and P. utilis) may pose sustainability concerns (Essandoh et al, 2023).…”
Section: Medicinal Use Of Eoppsmentioning
confidence: 99%
“…In Southern Ghana, local communities around Kakum National park uses the stem bark decoction of A. klaineana to treat malaria [ 21 ]. In-addition, recent studies by Essandoh PK et al also reported that local villages around Ankasa Forest Reserve, Western Ghana uses both the bark and root to treat malaria [ 22 ]. The stem bark decoction of this plant is also reported to be used in treating schistosomiasis in Atwima Nwabiagya district in Ghana [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants serve a variety of purposes, including being a vital and nutrient-rich source of food, a storehouse of medicinal compounds, an integral part of animal feed, a renewable energy source, a raw material for the production of charcoal, a medium for handicrafts, and a necessary component of construction activities (Boakye et al 2023;Metananda et al 2023;Muhesi et al 2023). Various plant species have been identified and explored as potential traditional medicines for the treatment of several illnesses and for other derivative products (Arshad et al 2023;Essandoh et al 2023;Soussi et al 2023). The traditional knowledge of such uses and practices has always been disseminated orally from generation to generation (Partasasmita et al 2019).…”
Section: Introductionmentioning
confidence: 99%